2012
DOI: 10.4161/cam.20154
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted roles of Eph/ephrin signaling in breast cancer

Abstract: Eph receptors and their membrane-bound ligands are intimately involved in the control of morphogenic processes during embryonic development and adult tissue homeostasis. By their ability to orchestrate cell migration, pattern formation and tissue integrity they are also prone to be involved in carcinogenic growth. In this review we concentrate on their involvement in the normal and carcinogenic development of the breast. In this context we summarize their multi-faceted functions as tumor suppressors, tumor pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 73 publications
1
41
0
1
Order By: Relevance
“…Eph receptors require direct cell-to-cell interaction for activation and they are divided into EphA and EphB receptor classes, depending on their preferential binding affinity for ephrinA or ephrinB ligands. Eph receptors have been documented in cancer (51), but the ligands have not been thoroughly investigated and in particular there is limited data on ephrinB1. However, a recent study has shown that enhanced expression of ephrinB1 is associated with lymph node metastasis and poor prognosis in breast cancer (52).…”
Section: Discussionmentioning
confidence: 99%
“…Eph receptors require direct cell-to-cell interaction for activation and they are divided into EphA and EphB receptor classes, depending on their preferential binding affinity for ephrinA or ephrinB ligands. Eph receptors have been documented in cancer (51), but the ligands have not been thoroughly investigated and in particular there is limited data on ephrinB1. However, a recent study has shown that enhanced expression of ephrinB1 is associated with lymph node metastasis and poor prognosis in breast cancer (52).…”
Section: Discussionmentioning
confidence: 99%
“…The Ephrin-A/EFNA subfamily of ligands is displayed on the cell surface via a glycosyl phosphatidylinositol (GPI) anchor (18). The ability of GPI-anchored proteins to internalize has been debated, yet several clinical-stage ADCs target such proteins (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Reverse signaling to the ligand (Ephrin)-expressing cell can accompany forward signaling to the Eph-expressing cell; however, the mechanisms underlying these signaling cascades remain unclear (17)(18)(19). The Ephrin/Eph family is implicated in breast cancer, where expression of several members inversely correlates with survival (18,20). These observations, coupled with the established role of Eph signaling in cancer, have resulted in numerous targeted therapeutics that have advanced to clinical trials; the majority of which are tyrosine kinase inhibitors (TKI; refs.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to a hypothesis that ephrinB2 mediated EphB4 activation and a balanced expression of receptor and ligand lead to tumor suppression [16]. This hypothesis was further supported by Noren et al, in which they reported activation of a tumor suppressor signaling pathway, Abl-Crk, downstream of ephrinB2/EphB4 signaling in breast cancer cells [17].…”
Section: Introductionmentioning
confidence: 95%